Effects of adipose allograft matrix on viability of humeral head cartilage and rotator cuff tendon - Andrea Karen Persons; Michael R. Baria; Ryan Rauck; Tyler Barker; Zarah Belacic; Sunjit Neginhal; Sushmitha Durgam (BMC Musculoskeletal Disorders)
Abstract Background Rotator cuff repairs may fail because of compromised blood supply, suture anchor pullout, or poor fixation to bone. To augment the repairs and promote healing of the tears, orthobiologics, such a platelet-rich plasma (PRP), and biologic scaffolds have been applied with mixed results. Adipose allograft matrix (AAM), which recruits native cells to damaged tissues, may also be a potential treatment for rotator cuff tears. Methods To assess the potential use of AAM on rotator cuff tears, humeral head cartilage and subscapularis tendon were collected from patients undergoing reverse shoulder arthroplasty (RSA). Punch biopsies of the tissues were used to create explants for tissue culture, and the remaining tissue was digested to isolate the chondrocytes and tenocytes for cell culture. Explants and cells were then cultured in media containing AAM. After 48 h, the tissues and cells were measured for cell viability, cell proliferation, extracellular matrix (ECM) and metalloproteinase (MMP) gene expression and for MMP, inflammatory cytokine, and growth factor concentrations. Results Cell viability was increased in humeral head chondrocytes and rotator cuff tenocytes cultured with AAM. Gene expression of the matrix proteoglycan, aggrecan, and of the proteolytic enzyme MMP-13 were downregulated in humeral head chondrocytes. MMP-13 concentrations were increased in subscapularis tenocytes and in humeral head chondrocyte/subscapularis tenocyte co-cultures. The anti-inflammatory cytokine, IL-1ra was increased in cartilage/tendon explant co-cultures. TGF-β1 concentrations were increased in chondrocytes, but decreased in tenocytes. Conclusions Overall, AAM had no significant negative effects on the cells or explants. The results of these experiments provide the basis for the future use of AAM as a scaffolding for tissue engineering, preclinical animal models of rotator cuff tear and glenohumeral osteoarthritis, and clinical models. Clinical trial number Not applicable.